Digital Capitalism. Media, Communication and Society Volume Three - Fuchs, Christian

Digital Fascism. Media, Communication and Society Volume Four - Fuchs, Christian

Foundations of Critical Theory. Media, Communication and Society Volume Two - Fuchs, Christian

Marxism and Identity - Fuchs, Christian (Searching for a Self. Identity in Popular Culture, Media and Society)

Verschwörungstheorien in der Pandemie. Wie über COVID-19 im Internet kommuniziert wird - Fuchs, Christian

交往资本主义：迈向马克思主义交往理论的批判 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences))

数字资本主义和大数据时代的卢卡奇 - Fuchs, Christian (马克思主义与现实 (Marxism & Reality) 年第5期. (shortened article version))

数字、传播与社会主义 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends))

社交媒体中的数字产消劳动：基于资本主义时间范畴的研究 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (4))

H παρακολούθηση των Κοινωνικών Μέσων - Fuchs, Christian (Η νέα ψηφιακή παρακολούθηση. Κείμενα προς τιμήν του Μηνά Σαματά (in Greek, The New Digital Surveillance: A Volume in Honour of Minas Samatas),)

Geburtstage: Manfred Knoche 80 Jahre - Fuchs, Christian (Publizistik)

Journalismus aus marxistischer Perspektive - Fuchs, Christian (Journalismustheorien)

Der Tod und die Liebe: Die Metaphysik der Kommunikation - Fuchs, Christian (Soziale Ordnungen des Sterbens)

Bildungspolitische und einzelschulische Entwürfe von Bildung in Differenzverhältnissen. Mediatisierungstheoretische Analysen im Kontext qualitativ vergleichender Forschung - Hummrich, Merle; Dehmel, Lukas (Schulkulturen in Migrationsgesellschaften. Studien zu Differenzverhältnissen im deutsch-amerikanischen Vergleich)

Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik. 2. Auflage)

Sichere Räume, reparative Kritik. Überlegungen zum Arbeiten mit verletzendem Material - Shnayien, Mary (Zeitschrift für Medienwissenschaft)
Medienwissenschaftliche Forschung zu tagesaktuellen Themen ist oft damit konfrontiert, große Mengen an antisemitischem, rassistischem, misogynem, verschwörungstheoretischem Material sichten und analysieren zu müssen, dessen Verletzungspotential auch die jeweiligen Forscher_innen negativ affiziert. Der Beitrag fragt nach möglichen Bewältigungsstrategien, mit denen sich zu verletzendem Material forschen lässt, und die eine wirkungsvolle Kritik desselben ermöglichen, ohne als Forscher_in in die vom Material ausgehenden negativen Affekte und Epistemologien verwickelt zu werden.

Lab Books - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

Die unsicheren Kanäle. Negative und queere Sicherheit in Kryptologie und Informatik - Shnayien, Marie-Luise

Resilienz durch Integration freiwilliger Helfer*innen in den Katastrophenschutz: organisationale und (forschungs-)politische Perspektiven - Hälterlein, Jens; Kaufmann, Stefan (Resilienz als Prozess)

Occupy the Internet: Why we need a Public Service Internet - Unterberger, Klaus; Fuchs, Christian (Building a European Digital Public Space: Strategies for Taking Back Control from Big Tech Platforms)

Social Media, Alienation, and the Public Sphere - Fuchs, Christian (The Social Media Debate: Unpacking the Social, Psychological, and Cultural Effects of Social Media)

大数据、社交媒体和数字异化 - Fuchs, Christian (国际社会科学杂志 (Journal of International Social Sciences) 2022 (5))

Servizio Pubblico - Fuchs, Christian (Wired Italia 102)

Digital Humanism. A Philosophy for 21st Century Digital Society. SocietyNow Series - Fuchs, Christian

Transform the Internet: Why we Need a Public Service Internet - Fuchs, Christian; Unterberger, Klaus (Public Value Texte)

Algorithms as complementary abstractions. Published online first 2022 - Matzner, Tobias (New Media & Society)

Hannah Arendt: Challenges of Plurality - Matzner, Tobias; Robaszkiewicz, Maria

Thomas Nyckel, Isabel Schmiedel, und Florian Sprenger - Shnayien, Marie-Luise; Engemann, Christoph (The Lab Book. Situated Practices in Media Studies)

ROBOTER BAUEN, PROGRAMMIEREN LERNEN, DIGITALE KULTUREN VERSTEHEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über Arduino in medienwissenschaftlicher Lehre und Forschung - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

FORSCHUNG (BE-)SCHREIBEN — Christoph Engemann, Sylvia Kokot, Thomas Nyckel, Isabel Schmiedel, Mary Shnayien, Florian Sprenger über medienwissenschaftliche Laborbücher - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (Open Media Studies Blog)
Die Sonderreihe zu Forschen, Lehren und Lernen mit digitalen Tools setzt sich mit zwei Beiträgen aus dem Bochumer Virtual Humanities Lab (VHL) fort. Im ersten Teil geht es um das auf Obsidian beruhende Laborbuch, das die Forschungsprozesse und Forschungsdaten am VHL dokumentiert, vernetzt und veröffentlicht. Explizites Ziel ist es, damit auch die Sackgassen, Wiederholungen und Umwege dieser Forschung sichtbar zu machen. Der zweite Teil stellt Arduino-Bausätze vor, wie sie am VHL in Forschung und Lehre eingesetzt werden, um in der Hands-on-Auseinandersetzung mit informatischen und ingenieurwissenschaftlichen Artefakten und Methoden einen erweiterten Zugang zu digitalen Kulturen zu eröffnen.

Arduino - Engemann, Christoph; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Mary; Sprenger, Florian (The Lab Book. Situated Practices in Media Studies)

FORSCHUNG (BE-)SCHREIBEN - Engemann, Christoph; Kokot, Sylvia; Nyckel, Thomas; Schmiedel, Isabel; Shnayien, Marie-Luise; Sprenger, Florian (Open Media Studies)

Institutionen der Medienpädagogik. Erwachsenen- und Weiterbildung - Meister, Dorothee M.; Dehmel, Lukas (Handbuch Medienpädagogik.)

(De)Coding Social Practice in the Field of XAI: Towards a Co-constructive Framework of Explanations and Understanding Between Lay Users and Algorithmic Systems - Finke, Josefine; Horwath, Ilona; Matzner, Tobias; Schulz, Christian (Artificial Intelligence in HCI)

Animation und Mimesis. Zur digitalen Expansion bewegtbildlicher Mimesis und ‚animimetischem‘ Denken - Eckel, Julia (Mimesis Expanded. Die Ausweitung der mimetischen Zone)

Digitalisierte Lernwelten. Neue Herausforderungen für die elterliche Unterstützung bei der Medienkompetenzentwicklung von Heranwachsenden - Teichert, Jeannine; Gerhardts, L.; Richter, L.; Meister, Dorothee M.; Kamin, A.M. (Empirische Pädagogik)

Minds in Motion – Some Basic Thoughts on AI and Animation - Eckel, Julia; Ehrlich, Nea (In: animationstudies 2.0)

animationstudiesblog 2.0 | Theme: AI and Animation

Intelligence In Between – Documenting AI in Animation - Eckel, Julia (animationstudies 2.0)

Bildungspolitische und einzelschulische Entwürfe von Bildung in Differenzverhältnissen. Mediatisierungstheoretische Analysen im Kontext qualitativ vergleichender Forschung - Hummrich, Merle; Dehmel, Lukas (Schulkulturen in Migrationsgesellschaften. Studien zu Differenzverhältnissen im deutsch-amerikanischen Vergleich)

Zweierlei Homophilie: Wendy Hui Kyong Chun und Leo Bersani - Althoff, Sebastian (Mimesis Expanded: Die Ausweitung der mimetischen Zone)

Musterbildungen. Ein alternativer Zugang zur Fernsehgeschichte: Über Lynn Spigels TV Snapshots – An Archive of Everyday Life - Miggelbrink, Monique (Cargo H. 56)

Teilen und die mediale Logik des Dabei-seins - Bartz, Christina (Following. Ein Kompendium zu Medien der Gefolgschaft und Prozesse des Folgens)

Technological Expectations and the Making of Europe - Hälterlein, Jens (Science & Technology Studies)
In a case study approach, the paper traces how technological expectations have been influential in the creation of European institutions, R&D programmes and regulatory instruments and how they have contributed to processes of European integration. The first case study shows how the promises of a coming ‘Atomic Age’ have been mobilized to support the foundation of the European Atomic Energy Community and, thus, contributed to European integration in the post-WW2 era. The second case study analyses how the security stream within the EU’s framework programmes for R&D is shaped by the promise of ‘technosecurity’ and enacts the normative claim of the EU’s security integration in the post-Cold War era. The third case study analyses how the EU’s AI strategy and AI act articulates the vision of a ‘human-centric AI’ and how this vision is related to the EU’s current attempt to restore citizens’ trust in times of crisis.
Keywords: History and Philosophy of Science

Theoriepolitiken des Überlebens: Trauerarbeit mit Lauren Berlant - Degeling, Jasmin; Hohmann, Philipp (Texte zur Kunst 126. Trauern. Mourning)

(De)Coding social practice in the field of XAI: Towards a co-constructive framework of explanations and understanding between lay users and algorithmic systems - Finke, Josefine; Horwath, Ilona; Matzner, Tobias; Schulz, Christian (Artificial Intelligence in HCI)

Reziprozität und das alteritäre Dritte – Über die wechselseitigen Verflechtungen von PageRank und sozialen Medien - Schulz, Christian (Behemoth . A Journal on Civilisation)

Mediale Fluidität oder fluide Medialität? Eine kurze Geschichte des Social-Media-Feeds - Schulz, Christian; Allekotte, Ann-Kathrin (Fluide Mediale. Medialität, Materialität und Medienästhetik des Fluiden)

PATTERNS 2022 The Fourteenth International Conferences on Pervasive Patterns and Applications

Well-being in Plastic Surgery: Deep Learning Reveals Patients' Evaluations - Kersting, Joschka; Geierhos, Michaela (Proceedings of the 10th International Conference on Data Science, Technology and Applications (DATA 2021))

Human Language Comprehension in Aspect Phrase Extraction with Importance Weighting - Kersting, Joschka; Geierhos, Michaela (Natural Language Processing and Information Systems)
In this study, we describe a text processing pipeline that transforms user-generated text into structured data. To do this, we train neural and transformer-based models for aspect-based sentiment analysis. As most research deals with explicit aspects from product or service data, we extract and classify implicit and explicit aspect phrases from German-language physician review texts. Patients often rate on the basis of perceived friendliness or competence. The vocabulary is difficult, the topic sensitive, and the data user-generated. The aspect phrases come with various wordings using insertions and are not noun-based, which makes the presented case equally relevant and reality-based. To find complex, indirect aspect phrases, up-to-date deep learning approaches must be combined with supervised training data. We describe three aspect phrase datasets, one of them new, as well as a newly annotated aspect polarity dataset. Alongside this, we build an algorithm to rate the aspect phrase importance. All in all, we train eight transformers on the new raw data domain, compare 54 neural aspect extraction models and, based on this, create eight aspect polarity models for our pipeline. These models are evaluated by using Precision, Recall, and F-Score measures. Finally, we evaluate our aspect phrase importance measure algorithm.

Artificial Intelligence and the Sociotechnical Imaginary: On Skynet, Self-Healing Swarms and Slaughterbots - Weber, Jutta (Drone Imaginaries. The Power of Remote Vision)

From Optimizing Military Operations to Targeting Terrorist Networks: Social Network Analysis in Data-Driven Warfare - Weber, Jutta; Mayer, Katja (Explorations in Digital Cultures)

Human-Machine Learning und Digital Commons - Weber, Jutta (In digitaler Gesellschaft. Neukonfigurationen zwischen Robotern, Algorithmen und Usern)

Auto-Mobilitätsmanagement? Über eine gelebte Vision Zero, repetitive Fortschrittsversprechen und gerechte Mobilität - Weber, Jutta (Autonome Autos. Medien- und kulturwissenschaftliche Perspektiven auf die Zukunft der Mobilität)

Expanding Technosecurity Culture. On Wild Cards, Imagination and Disaster Prevention - Weber, Jutta (Sensing In/Security: Sensors and the Making of Transnational Security Infrastructures)

Artificial Intelligence in the Age of Technoscience - Weber, Jutta (Routledge Social Science Handbook of Artificial Intelligence)

Das Audioviduum. Eine Theoriegeschichte des Menschenmotivs in audiovisuellen Medien - Eckel, Julia

The Public Service Media and Public Service Internet Utopias Survey Report - Fuchs, Christian (The Public Service Media and Public Service Internet Manifesto)

Communicating COVID-19. Everyday Life, Digital Capitalism, and Conspiracy Theories in Pandemic Times. SocietyNow Series - Fuchs, Christian

History and Class Consciousness 2.0: Georg Lukács in the Age of Digital Capitalism and Big Data - Fuchs, Christian (Information, Communication and Society)

Marxist Humanism and Communication Theory. Media, Communication and Society Volume One - Fuchs, Christian

Engels@200: Friedrich Engels and Digital Capitalism. How Relevant Are Engels’s Works 200 Years After His Birth? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Engels@200: Friedrich Engels in the Age of Digital Capitalism. Introduction - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Cornel West and Marxist Humanism - Fuchs, Christian (Critical Sociology)

Das digitale Kapital. Zur Kritik der politischen Ökonomie des 21. Jahrhunderts - Fuchs, Christian

The Public Service Media and Public Service Internet Manifesto

Social Media: A Critical Introduction. Third English edition - Fuchs, Christian

The Future of Public Service Media and the Internet - Alessandro, D'Arma; Fuchs, Christian; Horowitz, Minna; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

Introduction - Fuchs, Christian; Unterberger, Klaus (The Public Service Media and Public Service Internet Manifesto)

The Digital Commons and the Digital Public Sphere: How to Advance Digital Democracy Today - Fuchs, Christian (Westminster Papers in Communication and Culture)

How Did Donald Trump Incite a Coup Attempt? - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Foundations of Communication/Media/Digital (In)Justice - Fuchs, Christian (Journal of Media Ethics)

Channel 4: Rather Than Privatising Public Service Media We Should Be Expanding It Online - Fuchs, Christian (The Conversation)

数字劳动与卡尔·马克思 - Fuchs, Christian

Enformasyon Çağında Marx Okumak. Kapital Cilt 1 Üzerine Bir Medya ve İletişim Çalışması - Fuchs, Christian

Soziale Medien und kritische Theorie. Second German edition - Fuchs, Christian

Membaca Kembali Marx Di Era Kapitalisme Digital - Fuchs, Christian

Dijital Kapitalizm Çağında Marx’ı Yeniden Okumak. BeneDijital Kapitalizm Çağında Marx’ı Yeniden Okumak - Fuchs, Christian

受众商品、数字劳动之争、 马克思主义政治经济学与批判理论 (The Audience Commodity, the Digital Labour Debate, Marxist Political Economy, and Critical Theory). - Fuchs, Christian (国外社会科学前沿 (International Journal of Social Science) 2021 (4))

Dijital Nesneler, Digital Özneler - Büyük Veri Çağında Kapitalizm, Emek ve Siyaset Üzerine Disiplinlerarası Yaklaşımlar

弗洛姆与交往批判理论 - Fuchs, Christian (国外理论动态 (Foreign Theoretical Trends) 2021 (3))

Preface: Manfred Knoche’s Critique of the Political Economy of the Media and Communication [Preface to the article “Media Concentration” by Manfred Knoche] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Die Fussgänger*innen autonomer Kraftfahrzeuge. Eine informatische Dispositivanalyse - Matzner, Tobias (Autonome Autos – Die Zukunft des Verkehrs und die Dispositive der Mobilität)

Subjektwissen als Bildungsperspektive junger Erwachsener. Self-Tracking-Apps als digitale Optimierungstechnologien im Spannungsgefüge von Kontrolle und Selbstermächtigung - Burgfeld-Meise, Bianca; Dehmel, Lukas (Zeitschrift MedienPädagogik 42)

Engels@200: Friedrich Engels in the Age of Digital Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

卡尔·马克思与互联网研究 - Fuchs, Christian; Dyer-Witheford, Nick (国际社会科学杂志 (Journal of International Social Sciences) 2021 (9))

Die berufliche Tabletaneignung von Lehrkräften als Beispiel der Mediatisierung pädagogischer Handlungskontexte. Theoretische Perspektiven und empirische Befunde - Gerhardts, Lara; Dehmel, Lukas; Meister, Dorothee M. (Jahrbuch Medienpädagogik 16. Medienpädagogik in Zeiten einer tiefgreifenden Mediatisierung)

Zur Entgrenzung der Arbeit des medienpädagogischen Weiterbildungspersonals im Kontext tiefgreifender Mediatisierung - Dehmel, Lukas (Erwachsenenpädagogische Digitalisierungsforschung. Impulse - Befunde - Perspektiven. Bielefeld)

Epistemologies of predictive policing: Mathematical social science, social physics and machine learning - Hälterlein, Jens (Big Data & Society)

Mediating close friendship intimacy in times of (social) distance - Teichert, Jeannine (Networking Knowledge)

Francesco (Franz) Stefani - Ein Regisseur mit barocken Anklägen. - Ahrens, Stephan (Lichtspiele. Kino und Film im Brucker Land von den Anfängen bis zum Siegeszug des Fernsehens.)

Hermann Kappelhoff, Christine Lötscher, Daniel Illger (Hg.): Filmische Seitenblicke. Cinepoetische Exkursionen ins Kino von 1968. Berlin, Bosten: De Gruyter 2018 - Ahrens, Stephan (In: Filmblatt 25:73/74)

Christina Gerhardt, Marco Abel (Hg.): Celluloid Revolt. German Screen Cultures and the Long 1968. Rochester: Camden House 2019 - Ahrens, Stephan (In: Filmblatt 25:73/74)

Sammler und Beobachter. Das Programm der diesjährigen Internationalen Kurzfilmtage Oberhausen, Dschungel (jungle World) - Ahrens, Stephan (Kinema Kommunal, Nummer 2, Juni 2021)

Guy Gilles und das Kino der Entwurzelung - Ahrens, Stephan (In: Filmdienst, 24.08.2021)

Biografie Cox Habbema - Ahrens, Stephan

Biografie Peter Rabenalt - Ahrens, Stephan

Bilden mit/zu Animation - Bruckner, Franziska; Eckel, Julia; Feyersinger, Erwin; Freisleben-Teutscher, Christian F.; Ohnmacht, Tina (In Wirklichkeit Animation …)

Tech Demo/Tech Doku. Zur Wirklichkeit des Animierens - Eckel, Julia (In Wirklichkeit Animation ...)